2017
DOI: 10.3141/2648-03
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-Based Comparison of Holding Strategies for a Multibranch Light Rail Service

Abstract: Light rail transit services face many operational challenges, such as capacity constraints, mixed-traffic interference, and branch junctions. The service plans developed for these lines typically specify a precise schedule for each vehicle. Running time and demand variability, special events, and incidents make it challenging to adhere to schedules. Operators can enact real-time control actions to mitigate delays. This research compared the effectiveness of schedule- and headway-based holding strategies applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Rolling horizon optimization models have been used by Delgado et al ( 7 ) and Sánchez-Martínez et al ( 8 ) to simulate holding and dispatching times considering capacity constraints. Fabian and Sánchez-Martínez, using a simulation of the Green Line, found that headway-based dispatching at terminals resulted in shorter and more reliable passenger wait times than en route holding alone and holding by schedule ( 3 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Rolling horizon optimization models have been used by Delgado et al ( 7 ) and Sánchez-Martínez et al ( 8 ) to simulate holding and dispatching times considering capacity constraints. Fabian and Sánchez-Martínez, using a simulation of the Green Line, found that headway-based dispatching at terminals resulted in shorter and more reliable passenger wait times than en route holding alone and holding by schedule ( 3 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Real-time control actions, including holding, expressing, and short-turning, can be implemented in attempts of correcting headway variability as it occurs. Considering holding-type actions, previous simulation-based research shows that dispatching on headways at terminals yields the shortest and most reliable passenger wait times of any single control strategy ( 3 ).…”
mentioning
confidence: 99%
“…Only a few recent examples have examined real-time holding on a segment of overlapping lines. These studies focused on evaluating different operation schemes and on comparing regularity-based and schedule-based strategies (Hernández et al 2015;Fabian and Sánchez-Martínez 2017). The most relevant example in multiline control is the work of (Argote-Cabanero 2014; Argote-Cabanero, Daganzo, and Lynn 2015) who successfully extended the applicability of an isolated line holding criterion to multiline networks.…”
Section: Introductionmentioning
confidence: 99%
“…Simulation has been used extensively for evaluation of rail operations. Fabian et al ( 15 ), for example, utilized a data-driven mesoscopic simulation model to evaluate real-time holding strategies on a multi-branch rail system. The simulation results show that regularity and on-time performance could be improved using appropriate holding strategies.…”
mentioning
confidence: 99%